O dwóch adaptacjach "Mazepy" Juliusza Słowackiego - Kempna-Pieniążek, Magdalena (Śląskie Studia Polonistyczne, 2012)
On the example of Blanche by Walerian Borowczyk (1971) and Mazepa by Gustaw Holoubek (1975), the author of the article presents two different proposals of reading a drama by Juliusz Słowacki. As Holoubek’s work seems to be an attempt to look at person relationships presented in Mazepa from the angle of the categories close to psychoanalysis, Borowczyk’s film is dominated by a quasi-religious discourse. What plays an important role in the article is considerations on a different status of drama characters (especially that of Amelia and Blanche) in his adaptations and movie means by means of which the directors created their visions. Substantially different ways of reading Słowacki’s work point to two different adaptation strategies: where Borowczyk chooses a creative interpretation, Holoubek seems to look for hidden senses of drama.